(untitled) (Bangladesh Journal of Agricultural Research, 2018)
Heterosis for quantitative characters in 39 cucumber genotypes (19 parents and 20 F1 s) were investigated at the farm of Department of Genetics and Plant Breeding in Bangabandhu Sheikh Mujibur Rahman Agricultural University during March-November, 2013. Analysis of variance revealed highly significant differences among the parents and hybrids for 19 characters studied. Considerable coefficient of variation were observed for branches per plant, flesh thickness, placental thickness, fruit length ,fruit width, male and female flowers per plant, leaf length, leaf breadth, vine length, fruits per plant , fruit yield per plant indicating the scope of selection for those characters. The characters like branches per plant, male and female flowers per plant, fruit length, fruit weight, fruits per plant, fruit yield per plant contributed the maximum variability towards divergence among cucumber genotypes. Heterosis study depicted that the crosses Sobujsathi × Baromashi, Sobujsathi × Khira, Himaloy × Khira, exhibited significant positive heterosis for 50 % female flowering; Himaloy × Baromashi, Baromashi× Greenking for fruit length; Baromashi × Hero, Yuvraj × Khira for single fruit weight. Where Sobujsathi × Baromashi, Shila× Khira , Modhumoti × Hero and Modhumoti × Khira exhibited significant positive heterosis and heterobeltiosis for yield per plant. The highest positive heterotic effect for no. of fruits per plant was observed in Modhumoti × Baromashi (20%). The highest heterobeltiosis effect was found in hybrid Himaloy × Yuvraj (24.5%) followed by Sobujsathi× Khira (11.2 %), Modhumoti × Baromashi (10.0 %). Four crosses exhibited significant positive better parent heterotic effect for this trait and the combination Sobujsathi × Baromashi had the maximum heterosis on yield (47.6%). The maximum heterobeltiosis effect was found in Shila × Khira (27.73 %) followed by Modhumoti × Hero (15.14%) and Modhumoti × Khira (10%) for fruit yield. Bangladesh J. Agril. Res. 42(4): 731-747, December 2017